Thermal process and flow behavior during laser/ultra-high frequency (UHF) induction hybrid deposition. (15th August 2023) - Sun, Rui; Qiao, Yuhang; Yang, Yong; Liu, Guoliang; Shi, Yongjun; Fan, Kaijun; Wang, Qin
Highlight: A laser/ultra-high frequency (UHF) induction hybrid deposition method was proposed. A multi-field coupling numerical model was developed to study the deposition process. The UHF induction heat has pre-heating and slow-cooling effects on deposition process. The influence of the UHF induction parameters on the deposition process was analyzed. The UHF induction heat conduces to microstructure refinement of the deposited layer. Abstract: In this study, ultra-high frequency (UHF) induction heat was combined with laser deposition, which is referred to as laser–UHF induction hybrid deposition. On the one hand, this method takes the conventional laser induction hybrid deposition as reference, which uses the heat effect of UHF induction heat to optimize the residual stress of the deposited layer. On the other, this method utilizes the strong Lorentz force generated by the UHF induction heat to accelerate the flow velocity of the molten metal, which will be beneficial for microstructure refinement. Given that the thermal process and flow behavior during deposition are critical factors for the microstructure, a numerical model coupled with temperature field, electromagnetic field, flow field, and mass transfer field was developed to investigate the thermal process and flow behavior during laser–UHF induction hybrid deposition. Results showed that the UHF induction heat in laser-UHF induction hybrid deposition has pre-heating and slow-cooling effects on the deposited layer compared with laser deposition. The Lorentz force generated by UHF induction heat enhanced the flow velocity and the heat convection in molten pool. Research on the UHF induction heat parameters indicates that increasing the current frequency or current density can strengthen the slow-cooling effect of the UHF induction heat, and the flow velocity of the molten metal can be increased by 12.1% and 24.6%. Moreover, the maximum temperature in the molten pool decreased with increasing current frequency or current density because of the enhanced heat convection. Laser–UHF induction hybrid deposition experiment was also conducted, and the detected elemental content of the deposited layer and temperature showed good consistency with the simulated results. The grain size in the microstructure of the experimental laser–UHF induction hybrid deposited layer can be refined to approximately 3.358 μm at high current density conditions because of the enhanced fluid flow and heat convection in molten pool. This work provides an effective tool for predicting the thermal process and flow behavior during laser–UHF induction hybrid deposition, which will be an essential reference for evaluating microstructure quality.